Organizational Commitment Memperkuat Budget Participation Dengan Budgetary Slack - Hastuti, Sri; Yuliati, Anik (Jurnal Riset Ekonomi dan Bisnis, 2007)
Budget is one of instrument of management control and as primary component of financial planning on the future. Budget have two important roles, that’s in planning and control process. In order that budget processing can bring out budget which can function as planning and control instrument, mean not happened budgetary slack, so the manager center of accountability must participate (budget participation) in the budget processing. Not only required their participation in budget processing but also is needed their commitment (organization commitment) in budget execution.Base on description above, this research purpose to test effect of budget participation to budgetary slack, and to test moderate effect of organizational commitment which ability to strengthen relation between budget participation with Budgetary slack. To fulfill this research purpose, primary data applied in this research. These data analyzed by multiple regression approach through SPSS application program. Population in this research are managers of PT. PLN (Persero) Area Pelayanan dan Jaringan Surabaya Selatan, cited 23 managers. 23 managers are entirely becomes sampel of research. Result of this research indicates that : a) there is negative impact of service quality on customer satisfaction, but not significant,  b) there is positive impact customer-perceived value on customer satisfaction, and c) there is positive impact customer satisfaction on customer loyalty. Detail discussion, implication and limitation of this research will be explained under consideration following. Keywords : Organizational Commitment, Budget Participation, Budgetary Slack